The Influence Of Auditor Ethics, Competence And Experience On Audit Quality (In Public Accounting Firm (Kap) In West Java) - Aidah Intan Nabila; Teodora Winda Mulia (LP2M IAIN Palopo, 2026)
Audit quality is an important issue due to the increasing number of audit failures and violations of professional standards, which have reduced public trust in the public accounting profession. Therefore, auditors are required to possess professional ethics, adequate competence, and sufficient work experience to produce high-quality audits. This study aims to examine the effect of auditor ethics, auditor competence, and auditor work experience on audit quality at Public Accounting Firms (KAP) in West Java. This research employed a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to auditors working at Public Accounting Firms in West Java. The sample consisted of 45 auditors selected using a purposive sampling technique. The data were analyzed using descriptive statistical analysis, multiple linear regression analysis, coefficient of determination (R²), partial test (t-test), and simultaneous test (F-test) with the assistance of IBM SPSS Statistics version 29. The results indicate that auditor ethics and auditor work experience have a positive and significant effect on audit quality, whereas auditor competence does not have a significant effect on audit quality. Simultaneously, auditor ethics, auditor competence, and auditor work experience significantly affect audit quality. These findings imply that improving audit quality requires not only technical competence but also strong professional ethics and sufficient audit experience.